The Dialectic Image as a relevant category towards negative dialectics constelations: GOYA, GROSZ AND BENJAMIN / KLEE - Fallas-Vargas, Fabrizio (2018)
In this paper, the category of the dialectical image is explored as an analytical device. At a critical / praxical level, within this device, allegorical, graphic and especially conceptual elements are related to each other to develop a materialistic skepsis (a sine qua non component of constellations within dialectic´s in it´s negative/adornian expression). Somatic supports shown for this research are: Goya´s Caprice 43 (1799), Grosz´s The pillars of society (1926) and Benjamin´s Philosophy of History (Thesis IX), regarding Angelus Novus, Benjamin / Klee (1940/1920). Each one and by its own right can be seen from an adornian insight as intervention models that unequivocally reject the concealment, neutralization and / or displacement of its material / historical production conditions and therefore, they proceed to the dismantling of a mystified form of rationality that assumes and promotes the order of "the" culture as an incontrastable reality and fatal destiny.